ANALISIS KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU - Ahmad Khoiri (STAIN Bengkalis, 2024)
Increasing the quality of education is determined by the school principal's leadership. The school principal's leadership style greatly influences teachers' performance in carrying out their duties and responsibilities. This research aims to analyze school principals' leadership in improving teacher performance. The method used is qualitative with this type of research using literature reviews from articles, scientific journals, and books. The research results show that: School principal leadership in the era of globalization has experienced developments by utilizing digitalization to improve teacher performance. The leadership style is becoming more open, which impacts teacher performance to become more effective and efficient.